Geochemical characteristics of the eolian deposits in the Zoigê basin and their implications for provenance and weathering intensity. (30th June 2020) - Qi, Lin; Qiao, Yansong; Yao, Haitao; Wang, Yan; Peng, Shasha; Yang, Shuaibin
Abstract: Eolian deposits in the Zoigê basin at the northeastern region of the Tibetan Plateau (TP) were analyzed for their major-trace elements and SmNd isotopic compositions to explore the provenance and weathering intensity. The results are compared with the data from the Lingtai section (LT) in the Chinese Loess Plateau (CLP). Eolian deposits from different sections in the Zoigê basin have resembling geochemical compositions, reflecting similar provenance. Their major element compositions are close to those of the UCC, and their UCC-normalized major-trace element abundances and chondrite-normalized rare earth element (REE) abundances are similar to the LT samples. However, the SiO2, Al2 O3, TiO2, Zr, Hf, Sc, Co, V, Ni concentrations and SiO2 /TiO2, TiO2 /Al2 O3, Co/Th, La/Sc, Th/Sc, εNd (0), 147 Sm/ 144 Nd ratios of the Zoigê sections are quite different from those of the LT section, which suggests different provenances for the eolian deposits in these two regions. The relatively high abundances of SiO2, Zr, Hf and low abundances of trace elements indicate that local sediments on the TP are the major contributors to the eolian deposits in the Zoigê basin. Eolian deposits from the Zoigê basin have experienced the early Na and Ca removal stage, and chemical weathering parameters suggest a moderate weathering condition in the source and deposition regions.